Synthesis Of Tri Hydro Benzo /E/ 1,2-Oxatan-2,2 Dioxide (Latakia University Journal -Basic Sciences Series, 2018)
Some heterocyclic compounds of trihy dro-benzo compounds (e) 1-2 oxytin -2,2-dioxide of bipolar attachment reaction 1-4 were synthesis  for N-N, N-methyl methylene ethyl ketone and siphon in primary medium While maintaining the epoxy chain in the side chain. The structure of the resulting compounds was determined using spectral methods known as NMR spectroscopy, IR spectroscopy and the method of racial analysis. These compounds were obtained with a good yield ranging from (46-60%).